Antecedents of social media activism: an analytical study of a controversial topic. Issue 3 (17th February 2021) - Workman, Michael Dee
ABSTRACT: Using a data mining and deep machine learning technology and method, we conducted a multi-staged investigation of whether social media influenced people's opinions or merely confirmed already held beliefs, and furthermore, whether those social media conversations lead to people taking increasingly affirmative actions. We found that social media did tend to reinforce beliefs, but there were exceptions depending on certain personality antecedents. Additionally, the results were moderated by the affect intensity of participant sentiments. Building from these findings, we further studied whether or not people would take increasingly aggressive actions. We found that personality characteristics as an interaction with how strongly they felt about the subject, positively or negatively, did cause some people to take increasingly active measures.